Association of Metabolic Syndrome and its Components with Bladder Carcinoma: A Hospital-based Study - Syed Atif Hussain; Rukhsana Tumrani; Mehvish Sana; Anber Rahim; Afsheen Nigar; Seerat Fatima Tu Zahra (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: The study aims to evaluate the association of metabolic syndrome and its components with bladder carcinoma. Methods: Study conducted in Department of Urology, Sheikh Zayed Hospital, Rahim Yar khan from August 2021 to November 2023. A total of 139 study subjects aged between 20 to 80 years, histopathologically confirmed cases of bladder carcinoma with documented grade were evaluated for presence and absence of metabolic syndrome by clinical and laboratory examination and data was collected related to blood pressure, waist circumference, lipid profile and blood glucose fasting. Association was evaluated between metabolic syndrome and individual components of metabolic syndrome with bladder carcinoma. Metabolic syndrome was diagnosed according to the guidelines of National Cholesterol Education Program-Adult Treatment Panel III (NCEP-ATP III). Data was entered and analyzed by using SPSS version 23.   Results: Of the total 139 study subjects, 78 (56%) were having low grade bladder carcinoma and 61(44%) were diagnosed with high grade bladder carcinoma. Metabolic syndrome was present in 16 (11.5%) and absent in 123 (88.48%) study subjects. Metabolic syndrome was found with increased risk of bladder carcinoma (OR=1.544, 95% CI: 0.198-1.859). Odds ratio with 95% CI for bladder carcinoma was 1.206 (0.379-2.781) for central obesity, 1.215 (0.619-2.385) for triglyceride, 0.769 (0.386-1.532) for hypertension, 0.539 (0.260-1.117) for blood glucose fasting and 2.028 (0.665-6.183) for HDL-cholesterol. Increased risk of bladder carcinoma was found with central obesity, triglyceride and HDL-cholesterol. Association was found statistically significant (p value 0.010) between metabolic syndrome and bladder carcinoma.   Conclusion: On the basis of our study, a positive association has been found between metabolic syndrome and bladder carcinoma. Patients having metabolic syndrome should be screened for bladder carcinoma properly as early diagnosis and intervention prolong the survival of these patients.